Effect of surface modification of silica nanoparticles on toxicity and cellular uptake by human peripheral blood lymphocytes in vitro. Issue 3 (May 2011) - Lankoff, Anna; Arabski, Michal; Wegierek-Ciuk, Aneta; Kruszewski, Marcin; Lisowska, Halina; Banasik-Nowak, Anna; Rozga-Wijas, Krystyna; Wojewodzka, Maria; Slomkowski, Stanislaw
Abstract Silica nanoparticles have an interesting potential in drug delivery, gene therapy and molecular imaging due to the possibility of tailoring their surface reactivity that can be obtained by surface modification. Despite these potential benefits, there is concern that exposure of humans to certain types of silica nanomaterials may lead to significant adverse health effects. The motivation of this study was to determine the kinetics of cellular binding/uptake of the vinyl- and the aminopropyl/vinyl-modified silica nanoparticles into peripheral blood lymphocytes in vitro, to explore their genotoxic and cytotoxic properties and to compare the biological properties of modified silica nanoparticles with those of the unmodified ones. Size of nanoparticles determined by SEM varied from 10 to 50 nm. The average hydrodynamic diameter and zeta potential also varied from 176.7 nm (+18.16 mV) [aminopropyl/vinyl-modified] and 235.4 nm (−9.49 mV) [vinyl-modified] to 266.3 (−13.32 mV) [unmodified]. Surface-modified silica particles were internalized by lymphocytes with varying efficiency and expressed no cytotoxic nor genotoxic effects, as determined by various methods (cell viability, apoptosis/necrosis, oxidative DNA damage, chromosome aberrations). However, they affected the proliferation of the lymphocytes as indicated by a decrease in mitotic index value and cell cycle progression. In contrast, unmodified silica nanoparticles exhibited cytotoxic and genotoxic properties at high doses as well as interfered with cell cycle.